Apropos of a wax effi gy depicting Eros (Ἔρωςκήρινος): Carmen Anacreonteum 11 (Circe de clásicos y modernos, 2018)
Our aim is simply to define the magical qualities of a wax effigy depicting Eros as presented in the eleventh song of the anacreontic corpus. Since two different meanings are given to the word παντορέκτης (v. 11), we will argue that its sense here is ‘all-doing’, basing ourselves on the construction of similar magical figurines as described in other texts, as well as on the context of the anacreontic poetics.
Keywords: magic; Eros; anacreontic poetry; erotic constraint; oath